Egypt's workers: From protest movement to organized labor. A major challenge of the transition period - Nadine Abdalla (Stiftung Wissenschaft und Politik (SWP), 2012)
In the aftermath of the Egyptian revolution, the number of labor protests has increased sharply and added to an already dire economic situation. Undoubtedly, this escalation reflects both the culmination of the social problems in general and labor's representation crisis in particular. The organization of the labor movement via the establishment of new trade unions that are truly representative of the labor force would be the most effective solution. It would decrease the expansion of irregular workers' protests as well as help in realizing greater »social justice« - one of the main demands of the January 25 revolution and an essential component for stabilizing Egypt's transition. Moreover, the consolidation of new unions would be an important step toward the empowerment of civil society, and thus add to democratization. However, Egypt's new unions are facing several challenges that hinder their capacity to represent the workers effectively and keep them in a state of legal limbo. The lack of official recognition harms their legitimacy on the ground and they face several obstacles to the institutionalization process. Therefore, supporting the capacity-building of newly established trade unions is crucial for establishing an effective labor representation in Egypt and for supporting the Egyptian transition process
Keywords: 320